Assessing spatial disparities in Internet quality using speed tests - Paula Caldas, Maria (OECD Regional Development Papers, 2023)
The quality of Internet connections is increasingly important for people's daily lives as work and access to services move to the digital sphere. Likewise, businesses and public agencies need to rely more and more on the digital networks for service delivery. However, the way individuals experience the Internet can vary substantially within countries, notably along the urban-rural continuum. Measuring such variation in a consistent way is important to understand where intervention is most needed to deliver better connections to everyone. This paper assesses within-country spatial disparities in connectivity across OECD and G20 countries, using publicly available data on the speed of connections from an Internet speed test provider, applying consistent spatial definitions - i.e. the OECD classification of regions and the Degree of Urbanisation. Using data from Denmark, it finds that the use of speed tests to assess the quality of internet connection is coherent with national sources. Results show that, in OECD countries, regions far from metropolitan areas can experience up to 24% slower Internet speeds than the national average. Overall, cities have 75% higher speed of connection than rural areas, on average